2018
DOI: 10.1167/iovs.18-25245
|View full text |Cite
|
Sign up to set email alerts
|

Neural Plasticity Following Surgical Correction of Strabismus in Monkeys

Abstract: PurposeAlthough widely practiced, surgical treatment of strabismus has varying levels of success and permanence. In this study we investigated adaptive responses within the brain and the extraocular muscles (EOM) that occur following surgery and therefore determine long-term success of the treatment.MethodsSingle cell responses were collected from cells in the oculomotor and abducens nuclei before and after two monkeys (M1, M2) with exotropia (divergent strabismus) underwent a strabismus correction surgery tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…We did not find any difference in BCEA values before and after strabismus repair in patients with and without nystagmus. This is in agreement with a strabismic NHP study where no consistent changes of fixation instability were reported post strabismus repair 53 , 56 .…”
Section: Discussionsupporting
confidence: 93%
“…We did not find any difference in BCEA values before and after strabismus repair in patients with and without nystagmus. This is in agreement with a strabismic NHP study where no consistent changes of fixation instability were reported post strabismus repair 53 , 56 .…”
Section: Discussionsupporting
confidence: 93%
“…Surgery re-establishes the balance of power of the extraocular muscles. However, there are remodelling changes in both treated and untreated muscles [ 40 , 41 ] and adaptive responses within the neuron after patients undergo extraocular muscle surgery [ 42 ]. This may be related to the persistent exodrift and the high rate of under-correction after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Strabismus is one of the most common visual disorders, affecting the ability to maintain the alignment between the two eyes and therefore causing a binocularity breakdown due to the mismatch of the information provided by each eye to the visual cortex (Cullen, 2015). The importance of cortical mechanisms in the onset of strabismus is shown by the fact that, at least in monkeys, a lack of intervention at the cortical level can nullify the benefits brought by surgical treatment of the eye muscles (Pullela et al, 2018). Both in humans and other mammals, already the first weeks of life are fundamental for a proper oculomotor development leading to accurate eyes alignment (Tychsen, 2007).…”
Section: Strabismusmentioning
confidence: 99%